Scoliorhapis stepanovi—new species of sea cucumber from the North-West Pacific (Holothuroidea: Synaptida: Chiridotidae: Taeniogyrinae) and some remarks on the genus Scoliorhapis - Smirnov, Alexey V.; Panina, Elena G.; Sanamyan, Nadezhda P.; Sanamyan, Karen E. (Zootaxa, 2017)
New species Scoliorhapis stepanovi has been collected from depths of 10–23 m on the sandy bottom of Avacha Bay (east coast of Kamchatka), Paramushir Island (North Kuril Islands), and Matua Island (Middle Kuril Islands). It is unique in having sigmoid ossicles in the body wall with points at both ends (without an open-eye, and with the two points lying in a perpendicular plane). Such sigmoids do not occur in any other taeniogyrinid species. The two-pointed sigmoids are 80–115 µm in length, and are scattered in the body wall and not clustered. Probably the two-pointed sigmoids are underdeveloped typical sigmoid with open-eye. In the tentacles there are straight and C-shaped rods, sometimes branched at the ends, 70–90 µm in length. It is assumed that atypical two-pointed sigmoid ossicles may have been originated due to deviating from the usual course of sigmoid development in the middle stages. Scoliorhapis stepanovi resembles S. lindbergi. A key for species of Scoliorhapis is provided.